Immune system for the internet of things using edge technologies - Román-Castro, Rodrigo; Ríos-del-Pozo, Rubén; Onieva-González, José Antonio; López-Muñoz, Francisco Javier (My University, 2018)
The Internet of Things (IoT) and Edge Computing are starting to go hand in hand. By providing cloud services close to end-users, edge paradigms enhance the functionality of IoT deployments, and facilitate the creation of novel services such as augmented systems. Furthermore, the very nature of these paradigms also enables the creation of a proactive de- fense architecture, an immune system, which allows authorized immune cells (e.g., virtual machines) to traverse edge nodes and analyze the security and consistency of the underlying IoT infrastructure. In this article, we analyze the requirements for the development of an immune system for the IoT, and propose a security architecture that satisfies these requirements. We also describe how such a system can be instantiated in Edge Computing infrastructures using existing technologies. Finally, we explore the potential application of immune systems to other scenarios and purposes.
Keywords: Internet de los objetos; Arquitectura de ordenadores; Immune system; Internet of Things; Security; Cloud computing; Edge computing; Computer architecture; Task analysis